Features of Rehabilitation of Young Children with Severe Neurodevelopmental Delay Who Are Being Raised in Orphanages - O.M. Filkina; L.A. Pykhtina; S.B. Nazarov; T.G. Shaninа; Ye.A. Vorobyova; O.Yu. Kocherova; N.V. Dolotova (Zaslavsky O.Yu., 2013)
We observed 208 children from orphanages aged from 1 to 3 years, who suffered from mild-to-moderate perinatal affection of the central nervous system of hypoxic-ischemic origin. The objective of the study - the development of rehabilitation measures for young children with severe neurodevelopmental delay, who suffered from perinatal affection of the central nervous system, who are being raised in orphanages, on the basis of detected mechanisms of its formation. It is found that in the basis of the rehabilitation measures for children from orphanages with severe neurodevelopmental delay, who suffered from perinatal affection of the central nervous system, an integrated approach must lie, talking into account the presence of chronic stress in these children, associated with psychoemotional deprivation, that makes it possible to prevent further intensification of neurodevelopmental delay, deviations of physical development and reduce the incidence of background pathology.